Community Solar PV System for Sustainable Development in Thailand - Bangviwat, Athikom; Puapattanakul, Apinya (European Journal of Applied Sciences, 2025)
Cash flow analysis and System Advisory Model (SAM) are utilized to verify the economic viability of the investment in ground-mounted solar PV systems with various subsidy amounts. It has been found that a typical solar PV system with a capacity of 90 kWdc, which is adequate to supply daytime electricity for a community of 171 households, requires an investment of USD 135,555. With a 7% annual interest rate and 9.06% discount rate, a subsidy of 32.8% of the total investment is needed for break-even. In case the solar PV system is totally invested by the authorities, the revenue from the community’s residential users and the savings from payments to the electricity generators (SPP or VSPP) will be realized and result in an NPV of USD 600,480 at a discount rate of 9.06% and a 52% IRR. The payback period for the case where the authorities invest in the system is around three (3) years. By pro-rata, a total investment of USD 6,838.9 million is required to install solar PV of the total capacity of 4,540.6 MWdc to provide electricity for all residential customers of 8,627,138 households, which could reduce GHG of 4,450,306.3 tCO2e.